2018
DOI: 10.30684/etj.36.8a.1
|View full text |Cite
|
Sign up to set email alerts
|

Production of Lightweight Clay Bricks Using Polymer Wastes

Abstract: In this study, different percentages (2, 4, 6, 8, and 10% by weight of the soil) of chopped polymeric (plastic bottles with maximum particle size 2.36 mm and 1.18 mm in addition to rubber tires of 0.6 mm max particle size) wastes are incorporated with soil to produce lightweight clay bricks, to find the optimum percentage satisfying the requirements of bricks grade C using for non-structural walls (partitions).The effects of different types and percentages of the polymeric wastes on firing shrinkage, density, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is observed that compressive strength decreases with an increase in the plastic content, and at the same time, an increment in water absorption is witnessed. Al-Shathr and Al-Ebrahimy [73] introduced 2%, 4%, 6%, 8%, and 10% of PET waste plastic bottles by adding soil to it. It is observed that compressive strength decreases continuously with an increase in plastic content, while continuous increment in water absorption is recorded.…”
Section: Methodsmentioning
confidence: 99%
“…It is observed that compressive strength decreases with an increase in the plastic content, and at the same time, an increment in water absorption is witnessed. Al-Shathr and Al-Ebrahimy [73] introduced 2%, 4%, 6%, 8%, and 10% of PET waste plastic bottles by adding soil to it. It is observed that compressive strength decreases continuously with an increase in plastic content, while continuous increment in water absorption is recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Due to population growth, there is more solid trash than ever before. Polymer waste makes up a sizable component of all municipal solid waste [1]. Plastic is now being burned and deposited all over the world.…”
Section: Iraqi Journal Of Oil and Gas Researchmentioning
confidence: 99%
“…Before starting to explain the materials used and the way they are prepared, the figure (1) shows the progress of the paper and the method of work:…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation